2014
DOI: 10.1128/ec.00099-14
|View full text |Cite
|
Sign up to set email alerts
|

VeA Is Associated with the Response to Oxidative Stress in the Aflatoxin Producer Aspergillus flavus

Abstract: Survival of fungal species depends on the ability of these organisms to respond to environmental stresses. Osmotic stress or high levels of reactive oxygen species (ROS) can cause stress in fungi resulting in growth inhibition. Both eukaryotic and prokaryotic cells have developed numerous mechanisms to counteract and survive the stress in the presence of ROS. In many fungi, the HOG signaling pathway is crucial for the oxidative stress response as well as for osmotic stress response. This study revealed that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 48 publications
1
46
1
Order By: Relevance
“…A recent study performed in A. fumigatus suggested that AtfB might be regulated by SakA pathway and also demonstrated that atfB expression was dosedependently increased by using different concentrations of the antifungal agent caspofungin (Pereira Silva et al, 2016). In paralell, AtfB was demonstrated to be positively regulated by VeA (Baidya et al, 2014). By contrast, in our study, atfB was over expressed while veA levels were decreased suggesting that other factors may influence atfB expression.…”
Section: Piperine Inhibits Afb1 Production and Modulates Bzip Transcrcontrasting
confidence: 93%
See 1 more Smart Citation
“…A recent study performed in A. fumigatus suggested that AtfB might be regulated by SakA pathway and also demonstrated that atfB expression was dosedependently increased by using different concentrations of the antifungal agent caspofungin (Pereira Silva et al, 2016). In paralell, AtfB was demonstrated to be positively regulated by VeA (Baidya et al, 2014). By contrast, in our study, atfB was over expressed while veA levels were decreased suggesting that other factors may influence atfB expression.…”
Section: Piperine Inhibits Afb1 Production and Modulates Bzip Transcrcontrasting
confidence: 93%
“…In A. flavus, veA is also necessary for oxidative stress tolerance since it controls genes intervening in the HOG (high-osmolarity glycerol) signaling pathway. Indeed, veA deletion resulted in decreased transcription levels of several genes intervening in stress response such as srrA, msnA or atfA (Baidya et al, 2014).…”
Section: Piperine Impacts Cellular Signaling Receptors and The Globalmentioning
confidence: 99%
“…Treatment with BHA as also been shown to inhibit sclerotial differentiation in A. flavus . Oxidative stress responsive signaling mechanisms have been found to be involved in the regulation of aflatoxin production such as the stress responsive transcription factors AtfB, AP-1, and VeA (Reverberi et al, 2008; Sakamoto et al, 2008; Roze et al, 2011, 2013; Hong et al, 2013a,b; Baidya et al, 2014). Also, VeA along with VelB and LaeA form the Velvet protein complex to regulate both secondary metabolite production and reproductive development in A. flavus and other Aspergillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that chiB expression is altered in the veA deletion mutant also suggests possible alterations in cell wall composition in this A. flavus strain. This, together with the observed alterations in the expression of tpsA, encoding a phosphate synthase important in trehalose biosynthesis (68), could in part contribute the greater sensitivity to environmental stresses, such as oxidative stress, in the ⌬veA strain (69).…”
Section: Figmentioning
confidence: 99%